How risk communication affects public trust in government: the moderating role of policy expectations - Li, Nuoxue; Zeng, Weixi; Yin, Susu; Zhao, Lixia (Frontiers in Public Health, 2025)
IntroductionConspiracy narratives are a prevalent narrative framework in risk communication, often provoking public fear and defensive reactions, challenging the healthy interaction between governments and the public in social governance.MethodThrough two survey experiments, this study explores the effects of conspiracy narratives on public trust in government and the moderating role of policy expectations.ResultsIn Study 1 (N = 119), conspiracy narratives increased public perceptions of and concerns about the risks of genetically modified (GM) foods. As a result, the public was more likely to expect the government to adopt a strictly restrictive control policy on GM foods. Study 2 (N = 119) further reveals that public trust in the government increases when the public perceives the government as implementing a restrictive policy on GM foods. Conversely, public trust declines if the government is perceived to promote GM foods actively. Policy satisfaction plays a fully mediating role in this process.DiscussionThe study reveals the influence mechanism of conspiracy narratives on government trust, offering both a theoretical basis and practical recommendations for effective government communication and the development of harmonious government-public relations.